2013
DOI: 10.1002/hed.23385
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic approach to carcinoma of unknown primary

Abstract: Background The management of carcinoma of unknown primary (CUP) is one of the challenging conditions in head and neck oncologic surgery. Despite various diagnostic tools, the primary tumor site in more than half of cases remains unidentified. The purpose of this study was to assess the feasibility and efficiency of utilizing transoral robotic surgery (TORS) for the diagnosis and treatment of CUP in the head and neck. Methods In this prospective, single-institutional, clinical TORS trial, 22 of 181 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 20 publications
(64 reference statements)
3
94
0
4
Order By: Relevance
“…If a primary tumor is not found by this initial approach, for patients with level II or III lymph node metastases, ipsilateral tonsillectomy and base of tongue resection, by either transoral robotic surgery (TORS) or transoral laser surgery (TLM), is associated with a much higher rate of primary tumor detection and is now standard at many institutions. Reported primary tumor detection rates are up to 94 % for TLM (compared to 25 % for a traditional panendoscopic approach) and 77.3 % for TORS [26,27]. Some advocate bilateral tonsillectomy, since occult primary SCC may be found in the contralateral tonsil in a minority of cases.…”
Section: Squamous Cell Carcinoma Of Unknown Primary In the Era Of Hummentioning
confidence: 99%
“…If a primary tumor is not found by this initial approach, for patients with level II or III lymph node metastases, ipsilateral tonsillectomy and base of tongue resection, by either transoral robotic surgery (TORS) or transoral laser surgery (TLM), is associated with a much higher rate of primary tumor detection and is now standard at many institutions. Reported primary tumor detection rates are up to 94 % for TLM (compared to 25 % for a traditional panendoscopic approach) and 77.3 % for TORS [26,27]. Some advocate bilateral tonsillectomy, since occult primary SCC may be found in the contralateral tonsil in a minority of cases.…”
Section: Squamous Cell Carcinoma Of Unknown Primary In the Era Of Hummentioning
confidence: 99%
“…Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP. According to Durmus et al [41] the PT was identified in 77% of patients (17 of 22) with 80% HPV-positive LNM residing in the palatine tonsil in 59% (13 of 22), and the BOT in 18% (4 of 22). In a study by Channir et al [42] the PT was identified by TORS in 7/13 patients (54%) at the lingual tonsils with HPV-positive LNM in all of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Literatür bilgisi ışığında PBM' da primer lezyonu bulmak için transervikal USG ile hipoekoik lezyon aranmasının yararlı olabileceği söylenebilir (18). Literatürde PET-BT'de primer lezyon gösterilememiş ve transoral robotik cerrahi (TORS) ile lingual tonsillektomi yapılarak dil kökünde primer odağın saptandığı yayınlar mevcuttur (19)(20)(21). TORS ile lingual tonsillektomi PBM'da yeni bir uygulamadır ve primer lezyonu saptamada faydalı olarak görülmektedir (19)(20)(21).…”
Section: Lap Lokalizasyonu Ile Primer Lezyonun İlişkisiunclassified
“…Literatürde PET-BT'de primer lezyon gösterilememiş ve transoral robotik cerrahi (TORS) ile lingual tonsillektomi yapılarak dil kökünde primer odağın saptandığı yayınlar mevcuttur (19)(20)(21). TORS ile lingual tonsillektomi PBM'da yeni bir uygulamadır ve primer lezyonu saptamada faydalı olarak görülmektedir (19)(20)(21). Primer lezyonu saptamak için immünohistokimyasal ve moleküler çalışmalar yapılabilir.…”
Section: Lap Lokalizasyonu Ile Primer Lezyonun İlişkisiunclassified